Analysis of ecological prevention and control technology for expansive soil slope - Tao, Wenbing; Wen, Yingwen; Bian, Xia; Ren, Zhilin; Xu, Long; Wang, Fei; Zheng, Hu (Frontiers in Earth Science, 2024)
For the expansion soil slope in the JiangHuai area before the disposal of the neglect of expansion of the weak defects and slope disposal after the poor long-term stability of the current situation. This study investigates the ability of ecological slope protection technology to cope with the destabilizing geohazard of expansive soil slopes. Analyzing the collapse reasons of weak expansive soil slopes in the JiangHuai region based on the reinforcement project of expansive soil slopes along highways in the JiangHuai region, combined with actual engineering research, a “storage-resistance” water regulation ecological prevention and control technology is proposed. The feasibility and sustainability of the ecological slope protection technology is discussed in terms of its principles and influencing factors, and the protection effect is verified by combining numerical simulation and field test methods. Research findings suggest that the “storage-resistance” technology effectively prevents rainwater infiltration, particularly under light rain conditions, with continuous blocking capability. Under rainstorm conditions, it can prevent infiltration for about 4 h, significantly enhancing slope stability. Slope rate variations show no significant impact on reinforced slope stability, with maximum deformation occurring at the slope’s foot after rainfall. Reinforcement plans should prioritize strengthening support at the slope’s base. Proper selection and optimization of technical parameters can lead to more economical and sustainable solutions while extending protection time. Field trials confirm the suitability of the “storage and blocking” water regulation ecological control technology for the JiangHuai region, particularly where light rain prevails. These findings suggest that ecological control techniques for expansive soil slopes can effectively regulate slope moisture changes and reduce the geohazard risk of expansive soil slope instability.